2001
DOI: 10.1542/peds.107.6.e99
|View full text |Cite
|
Sign up to set email alerts
|

Deaths Attributed to Pediatric Complex Chronic Conditions: National Trends and Implications for Supportive Care Services

Abstract: ABSTRACT. Background. Children with complex chronic conditions (CCCs) might benefit from pediatric supportive care services, such as home nursing, palliative care, or hospice, especially those children whose conditions are severe enough to cause death. We do not know, however, the extent of this population or how it is changing over time.Objectives. To identify trends over the past 2 decades in the pattern of deaths attributable to pediatric CCCs, examining counts and rates of CCC-attributed deaths by cause an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
435
0
16

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(457 citation statements)
references
References 12 publications
6
435
0
16
Order By: Relevance
“…Complex chronic conditions were identified by presence of validated ICD-9 codes in the visit's billing record. 13 …”
Section: Methodsmentioning
confidence: 99%
“…Complex chronic conditions were identified by presence of validated ICD-9 codes in the visit's billing record. 13 …”
Section: Methodsmentioning
confidence: 99%
“…Children were identified as having a CCC if they had a diagnosis of a neuromuscular, cardiovascular, respiratory, renal, gastrointestinal, hematologic, metabolic, congenital, or cancer health condition based on an International Classification of Diseases, 9th Revision (ICD-9-CM) code as recommended by Feudtner et al 8 Duplicates and children who were not California residents were excluded from the sample. Our final sample size was 1423 children.…”
Section: Samplementioning
confidence: 99%
“…7 Previous studies have found that deaths among children with CCCs vary widely by type of health condition and age group. 5,8,9 The prevalence of children with CCCs in the inpatient hospital setting has increased, 10,11 and their EOL care in this setting is highly technical. 12 Accordingly, the average cost of health care services for these children ranges from $62,000 to $110,000 annually.…”
Section: Introductionmentioning
confidence: 99%
“…Discharge disposition is known to vary by age, with older children with chronic conditions being more likely to use hospice services compared with infants. 8 A recent study suggests that deaths outside the hospital have become increasingly common for older children over time, with the expansion of EOL supportive services in communities to meet the needs of families with gravely ill children. 8 Length of Stay, Hospital Charges, and Mortality Related to Insurance Status In this study, insured children who were admitted and died had significantly longer hospital stays compared to uninsured children who were admitted and died.…”
Section: Discussion Children's Inpatient Mortalitymentioning
confidence: 99%
“…8 A recent study suggests that deaths outside the hospital have become increasingly common for older children over time, with the expansion of EOL supportive services in communities to meet the needs of families with gravely ill children. 8 Length of Stay, Hospital Charges, and Mortality Related to Insurance Status In this study, insured children who were admitted and died had significantly longer hospital stays compared to uninsured children who were admitted and died. DRG diagnoses by payer were very similar among children who died, although it is possible that differences in length of stay by payer status may reflect differences in severity of illness at admission and/or processes of care during hospitalization, which could not be fully accounted for using diagnostic codes.…”
Section: Discussion Children's Inpatient Mortalitymentioning
confidence: 99%